Psychiatric and Physical Comorbidity in Elderly Attending the Geriatric Clinic of a Psychiatric Hospital - Jesmin, Humayra; Sarkar, Ahsan Aziz; Ahmed, Helal Uddin; Zannat, Hasinatul (Bangladesh Journal of Medicine, 2021)
Background: Physical comorbidity is quite common in older adults. When psychiatric and medical conditions co-occur, the combination is associated with elevated symptom burden, functional impairment, decreased length and quality of life, and increased costs of treatment. To estimate the proportion and patterns of physical comorbidity in elderly psychiatric patients. Methods: A retrospective observational study was carried out in the Geriatric Clinic of National Institute of Mental Health and Hospital (NIMHH). Patient registry of the clinic was used to collect required information and 113 consecutive older adults with psychiatric disorders who attended the clinic in a three-month period, were enrolled for the study. Psychiatric diagnoses were made by psychiatrists, according to DSM-5 criteria. Medical diagnoses were made by specialist physicians by reviewing physicians’ prescriptions. Data analysis was done by using SPSS 23.0. Results: Most of the patients (58.4%) belonged to the 7th decade. Among 113 patients 90 (79.7%) had only psychiatric illness & 23 had (20.4%) comorbid physical disorders. Depressive disorders (30%) and dementia (22.1%) were the most common psychiatric reasons for consultation. Among the associated physical comorbidities hypertension (43.5%) and diabetes (34.8%) were the most commons. Conclusion: Co-occurrence of psychiatric and physical disorder conditions is very common in a clinical setting. Physical comorbidity may influence follow up consultation pattern. Bangladesh J Medicine July 2022; 33(1) : 40-43